Comparable potency of IFNα2 and IFNβ on immediate JAK/STAT activation but differential down-regulation of IFNAR2 - Marijanovic, Zrinka (Portland Press Ltd., 2007)
Type I IFNs (interferons) (IFNα/β) form a family of related cytokines that control a variety of cellular functions through binding to a receptor composed of IFNAR (IFNα receptor subunit) 1 and 2. Among type I IFNs, the α2 and β subtypes exhibit a large difference in their binding affinities to IFNAR1, and it was suggested that high concentrations of IFNAR1 may compensate for its low intrinsic binding affinity for IFNα2. We tested whether receptor-proximal signalling events are sensitive to IFNAR1 surface concentration by investigating the relationship between relative IFNAR1/IFNAR2 surface levels and IFNα2 and IFNβ signalling potencies in several cell lines. For this, we monitored the activation profile of JAK (Janus kinase)/STAT (signal transducer and activator of transcription) proteins, measured basal and ligand-induced surface decay of each receptor subunit and tested the effect of variable IFNAR1 levels on IFNα2 signalling potency. Our data show that the cell-surface IFNAR1 level is indeed a limiting factor for assembly of the functional complex, but an increased concentration of it does not translate into an IFNα/β differential JAK/STAT signalling nor does it change the dynamics of the engaged receptor. Importantly, however, our data highlight a differential effect upon routing of IFNAR2. Following binding of IFNα2, IFNAR2 is internalized, but, instead of being routed towards degradation as it is when complexed to IFNβ, it recycles back to the cell surface. These observations suggest strongly that the stability and the intracellular lifetime of the ternary complex account for the differential control of IFNAR2. Moreover, the present study opens up the attractive possibility that endosomal-initiated signalling may contribute to IFNα/β differential bioactivities.